A Psicologia vai à escola : trabalho colaborativo com uma professora de educação infantil - Caneguim, Janaina de Fatima Castro (2016)
The teacher and its work have been the target of researchers and interventions, however, in some cases; this professional develops a little active role. Work proposals which discuss scholar questions along with teachers appear in a collaborative format, in which this professional would take an active role in the knowledge construction and there would be knowledge exchange among those involved. The Behavior Analysis provides conditions to the discussions about the process of teaching and learning including the description of principles and procedures which contributed for effective teaching, and, also, for descriptive function evaluation which can be understood as an educational resource that has been teaching the teachers, and, in which, an individual establishes functions relations between events from behavior identification to be analyzed and antecedent conditions and subsequent to this behavior. From a collaborative work format, the aims of this research were to describe teaching situations carried out by kindergarten teacher for teaching pre-arithmetic skills and also enable to the participant to describe functional relationships between what she wanted to teach, their teaching practices, and performance of their students as a result of its practices. In addition, to describe the present collaborative work, as well as, to create conditions for the teacher to describe principles and procedures for Behavior Analysis, which could contribute to effective teaching, were also aims of this study. The present work has conducted at the school where the teacher works. It was realized interviews to research teaching practices (in the context of teaching pre-arithmetic skills) for teaching pre-arithmetic skills; a discussion between researcher and participant on tasks present in an educational program of pre-arithmetical skills and teacher interaction with the mentioned program; recording and classroom observations; discussions for planning and analysis classes. It was described seven situations of teaching which will be used for the teaching pre-arithmetic skills from the data. However, only two teaching situations were also planned, executed and analyzed, which were related to the ordering skills of ensemble and notion of the pertinence of the objects to sets. The descriptive functional assessment seems to be a tool with potential to collaborative works with teachers. However, the procedure used did not allow that the participant functionally relates all the aspects discussed in the planning of the analyzed classes. The teacher showed indicative behaviors that appropriated elements brought by the researcher, in the other words, viii the participant used in some moments of the planning, execution and analysis of class principles and procedures described by Behavior Analysis focused on teaching (for example, she said that should have done the evaluation of the previous repertoire of students to realize a teaching situation). In addition, in these situations, the participant established some punctual dependence relations between theirs aims, teaching practices and performance measures for students on these practices. Because it was a collaborative work, the exchange knowledge between researcher and participant was something desired, and about this, the participant contributed describing practices for the pre-arithmetical skills teaching, as well as thinking of teaching opportunities for those who were not part of their routine. Participant speeches indicated that some elements of the collaborative work were not present throughout the interaction, such as the co-responsibility for the work. Changes in the present procedure were suggested to amend this characteristic of the interaction.